Factors that influencing an adoption of mobile banking: a case study in Kajang, Selangor / Muhammad Muhaimin Pozlan - Pozlan, Muhammad Muhaimin (Faculty of Business and Management, 2019)
The aim of this study is to determine the key factors that influence consumer to accept mobile banking. The study uses primary data, which means that the data and information would be gained from the respondents by using questionnaires. The factors involve in this study were attitude, perceived ease of use, perceived usefulness, behaviour control and subjective norm. The factors are taken based on previous study by previous researchers which is Aboelmaged & Gebba (2013) with Journal Adoption Mobile Banking: An Examination of Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). The data would be collected from the respondents through questionnaires distributed to them. 150 questionnaires would be answered by the respondents who qualified the criteria in this study. The data would be then only be collected from consumer in Kajang, Selangor due to the highest population was registered in Malaysia with 6.38 million of people was reported by Department of Statistics Malaysia (DOSM) in 2017. The data and information collected would be used to generate the analysis. Descriptive analysis, factor analysis, analysis of variance, reliability test and regression will be used to trigger the results of this study. By understanding the factor influencing consumer on mobile banking, it would be able to gauge the factor that matter most before using mobile banking. In this study found that, four variable significant which is attitude, perceived ease of use, perceived usefulness and behavioural control. However, only one variable insignificant which is subjective norm.